Off-seasonal copulation of South American sea lion Otaria byronia in the Chilean Central Coast - Guzmán , Jonathan A.; Torres, Patricio; Cañón, Carola; Sielfeld, Walter (Therya Notes, 2022)
The South American sea lion Otaria byronia inhabit almost continuously from Perú to southern Chile and Brazil to southern Argentina on the Pacific and Atlantic Oceans, respectively. It is an abundant species, with great vagility and reproductive success and, without conservation problems. Like all pinnipeds, O. byronia exhibits a reproduction, notedly seasonal and highly synchronized with slight interpopulation differences, being the description of an atemporal copulation the objective for this note. On September 2020 we carried out a field observation in a reproductive rookery of O. byronia through binoculars on a rock in the Chilean central Coast. Eight individuals of O. byronia were recorded; from them, a couple had courted each other by moving their heads and bodies in unison. Subsequently, the male (sub-adult) mounted the female and they copulated for approximately 20 minutes, after which, she unhurriedly jumped into the sea. During the courtship and copulation only the male emitted sounds, and no mutual aggressive behavior was observed, not even the female opposed to being copulated, nor the 6 other individuals interacted with both. Considering its reproduction during the austral summer, this off-seasonal copulation is unusual for O. byronia; unprecedented in Chilean populations and subcontinent, being aspects such as climatic, physiological to anthropogenic factors suggested as causes, or triggers for this event. The foregoing highlights the need to expand studies of marine mammals distributed on the Chilean coast and explore the link and impact of extrinsic factors on populations.